PRODUCTIVITY ANALYSIS USING THE COBB-DOUGLAS FUNCTION BASED ON EFFECTIVE WORKING HOURS - Dyah Ayu Shinta Permatasary; Tedjo Sukmono (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This research aims to compare the productivity of the amount of effective working time in the production department in 2021 and 2022. Method: The productivity measurement method is based on the Cobb-Douglas production function approach, so that we can know the extent of the company's efficiency and effectiveness. Productivity measurement is carried out using the Cobb-Douglas function approach. Results: This research shows that the level of productivity in 2022 is higher than in 2021 with the efficiency index values in 2021 and 2022 being 0.9499104 and 1.0599527. This means that the use of working hours increased by 11.58%. Novelty: These results can be used as consideration in maintaining and increasing productivity.